Assessing Knowledge, Skills and Capacities in Environmental Management: A Study on Bangladesh (The National University Journal of Humanities, Social Sciences and Business Studies, 2023)
In Bangladesh, there is a gap in environmental understanding, one of the most critical issues that make the development process extremely challenging. Therefore, Bangladesh needs adequate knowledge, capacity, and skills in environmental management. This objective warranted an assessment of available capacity and needs for specific knowledge and skills in environmental management. Data and information were collected from primary and secondary sources. The primary level information was collected through in-depth interviews and observation. For secondary information, both published and unpublished literature were studied. In Bangladesh, to address ever-increasing environmental problems, government interventions and policy initiatives, academic programmes, research initiatives, and environmental activism became quite visible in the mid-nineties of the last century. In the academic arena, two types of initiatives became prominent. First, the environmental dimension was added to some of the existing academic disciplines of different public universities to develop knowledge and skills. On the other hand, some public and private universities in Bangladesh introduced new academic programs specifically focusing on the environment. However, in public universities where environmental education has been introduced as an addition or extension to parent disciplines, only a limited number of courses on environmental management have been introduced. This has left aside other pertinent areas of environmental management from the purview of the educational programme. The disciplines that included environmental management in their domains still emphasize on their parent subject areas. Therefore, it is recommended to introduce a comprehensive education programme consisting of environmentrelated courses with suitable bearings on environmental management.NU Journal of Humanities, Social Sciences & Business Studies Vol. 7 & 8, No.2 & 1, July 2021 - December 2022 p. 23-38